Putting proficiency: contributions of the pelvis and trunk - Delphinus, E. M.; Sayersa, M. G. L. (Sports Biomechanics, 2012)
Putting proficiency is a key determinant of golfing success and yet minimal biomechanical research has been published on this important skill. Little is known about the motion and coordination of the pelvis and trunk during the putting motion. The purpose of this study was to present detailed three-dimensional (3D) kinematic profiles of the pelvis and trunk during the putting motion, and to determine if differences in kinematics exist between proficient and non-proficient golfers. A 3D analysis (100 Hz) was conducted on 10 single figure handicap golfers using a six-camera motion capture system. Participants completed 18 putts (2 m) towards a cup in an indoor facility and were subsequently divided into two groups based on putting proficiency (Proficient: >79%; Non-proficient: < 79%). Variables assessed were the linear movements of the centre of mass (COM) and head, and the angular movements of the pelvis and trunk. Effect size statistics showed that the Proficient putters tended to move predominantly in the frontal plane (towards the target), while the Non-proficient putters moved more sagittally. In addition, the Non-proficient putters recorded greater movement variability. The implications of this study suggest that putting proficiency is enhanced when the COM moves towards the target.